2023
DOI: 10.1101/2023.10.02.560557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut metabolite L-lactate supportsCampylobacter jejunipopulation expansion during acute infection

Ritam Sinha,
Rhiannon M. LeVeque,
Sean M. Callahan
et al.

Abstract: How the microaerobic pathogenCampylobacter jejuniestablishes its niche and expands in the gut lumen during infection is poorly understood. Using six-week-old ferrets as a natural disease model, we examined this aspect ofC. jejunipathogenicity. Unlike mice, which require significant genetic or physiological manipulation to become colonized withC. jejuni, ferrets are readily infected without the need to disarm the immune system or alter the gut microbiota. Disease afterC. jejuniinfection in ferrets reflects clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We have shown that cysteine residues of HpCemR become oxidised under O 2 -triggered oxidative stress in vivo and in vitro, which changes the protein’s DNA-binding activity possibly by structural changes of DNA-protein complex rather than on-off mechanism 22,24 . Recent studies on CjCemR interactions with the promoter region of lctP suggested a similar mechanism of CjCemR activity control and lctP transcription regulation 26 . AbCemR protein also contains cysteine residues, one of which is conserved in all three species (C27 in HpCemR and CjCemR, C31 in AbCemR).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown that cysteine residues of HpCemR become oxidised under O 2 -triggered oxidative stress in vivo and in vitro, which changes the protein’s DNA-binding activity possibly by structural changes of DNA-protein complex rather than on-off mechanism 22,24 . Recent studies on CjCemR interactions with the promoter region of lctP suggested a similar mechanism of CjCemR activity control and lctP transcription regulation 26 . AbCemR protein also contains cysteine residues, one of which is conserved in all three species (C27 in HpCemR and CjCemR, C31 in AbCemR).…”
Section: Discussionmentioning
confidence: 97%
“…HP1021 interacts with the origin of chromosome replication region ( oriC ), probably participating in the control of the initiation of H. pylori chromosome replication 25 . As for Cj1608, in vitro, it interacts with the C. jejuni oriC region and the promoter of the lctP lactate transporter, probably participating in the control of the initiation of the C. jejuni chromosome replication and lactate metabolism 26,27 .…”
mentioning
confidence: 99%